Penerapan Model Pembelajaran Teams Games Tournament dalam Meningkatkan Cara Berfikir Siswi - Fathor Rozi; Anissuhada' Anissuhada' (LP2M STIT Palapa Nusantara, 2022)
Teacher-Centered Learning that uses conventional methods often makes students bored and bored. This can be one of the causes of the inhibition of students' thinking abilities. The purpose of this study was to examine the application of the Teams Games Tournament (TGT) learning model so that the student's way of thinking became more honed and no longer bored during learning. This research uses the Classroom Action Research (CAR) method in its implementation. The research subjects were class VIII B Regular MTs N 1 Probolinggo, 24 students. Data collection techniques based on pre-test and post-test. The research model design is carried out through the following stages: planning action, implementing the action, observing/evaluating, and reflecting. The results show that the students have achieved the expected learning mastery, 75%. That is, the thinking level of students is getting higher so that the learning objectives that have been designed can be adequately achieved. This is evidenced by the average score of 80.25 students and 17 students who have completed their studies or 70.83%.